2022
DOI: 10.7554/elife.73521
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein-like pigments optimise the internal light environment in symbiotic reef-building corals

Abstract: Pigments homologous to the Green Fluorescent Protein (GFP) have been proposed to fine-tune the internal light microclimate of corals, facilitating photoacclimation of photosynthetic coral symbionts (Symbiodiniaceae) to life in different reef habitats and environmental conditions. However, direct measurements of the in vivo light conditions inside the coral tissue supporting this conclusion are lacking. Here, we quantified the intra-tissue spectral light environment of corals expressing GFP-like proteins from w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 111 publications
5
37
0
Order By: Relevance
“…There has been a special focus on coral skeletons and host pigments (e.g. Falkowski et al, 1984; Kühl et al, 1995; Wangpraseurt et al, 2014b; Lyndby et al, 2019; Kramer et al, 2021; Bollati et al, 2022). Studies have shown that in vivo light exposure of symbionts is modulated on a holobiont level to enhance photosynthesis, including alleviating photodamage and bleaching (Lesser and Farrell, 2004; Enriquez et al, 2005; Marcelino et al, 2013; Wangpraseurt et al, 2017), altering inter- and intracellular pH (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a special focus on coral skeletons and host pigments (e.g. Falkowski et al, 1984; Kühl et al, 1995; Wangpraseurt et al, 2014b; Lyndby et al, 2019; Kramer et al, 2021; Bollati et al, 2022). Studies have shown that in vivo light exposure of symbionts is modulated on a holobiont level to enhance photosynthesis, including alleviating photodamage and bleaching (Lesser and Farrell, 2004; Enriquez et al, 2005; Marcelino et al, 2013; Wangpraseurt et al, 2017), altering inter- and intracellular pH (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of animal chromoproteins (CPs) in the animal tissue, which is responsible for creating "colorful" bleached corals (Bollati et al, 2020;Bollati et al, 2022), has been proposed as one of the mechanisms for coral bleaching recovery. The most common group of animal CPs found in corals are the Green Fluorescent Proteins (GFP) (Matz et al, 1999;Salih et al, 2000;Alieva et al, 2008;Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The most common group of animal CPs found in corals are the Green Fluorescent Proteins (GFP) (Matz et al, 1999;Salih et al, 2000;Alieva et al, 2008;Smith et al, 2013). They are primarily found in populations of shallow areas, exposed to high-light environments, and their upregulation can be promoted by blue light (Salih et al, 2000;D'Angelo et al, 2008), nutrient stress (Bollati et al, 2022), and exposure to mild heat stress (Bollati et al, 2020). Animal CPs generally accumulate in parts of the coral colony with low symbiont density composition, such as the areas with the highest growth rate, or parts that are particularly damaged (Smith et al, 2013;Bollati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations